Pengembangan Bahan Ajar Berbasis Multimedia - Teguh Handoyo; I’anatul Ashriyah; Rahmat Kamal (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This article discusses the urgency of effective multimedia-based teaching materials in improving students' learning experience as a solution to the challenges of the times. By looking at the challenges of stagnant traditional education and the lack of utilization of technology in developing teaching materials. By utilizing various multimedia elements such as text, images, audio, and video, this research explores the use of multimedia on student motivation and understanding in the learning process. This article uses the Systematic Literature Review (SLR) method to explore various studies related to the use of Multimedia in the preparation of teaching materials. The results show that the use of multimedia-based teaching materials not only increases students' interest in learning but also significantly improves learning outcomes. Feedback from users shows that interactive and visual elements in learning materials are very helpful in understanding complex concepts. This study concludes that the integration of multimedia in education can be an effective strategy to improve the quality of learning in the digital era.